EVALUASI PENERAPAN PERHITUNGAN, PENETAPAN DAN PEMBAYARAN PAJAK AIR PERMUKAAN PADA PT AIR MANADO - Ropah, Tania; Alexander, Stanly W.; Mintalangi, Syermi S.E (GOING CONCERN : JURNAL RISET AKUNTANSI, 2021)
Surface water tax is a tax that is included in the authority of the local government which is one of the contributions to increase the Local Native Income (PAD) and collected by the level 1 (one) government or the provincial government. This study aims to evaluate the application of calculation, determination and payment of surface water tax by PT Air Manado. The analysis method used in this study is a descriptive analysis method whose method of data collection is through interviews and documentation. The results showed that the calculation and determination of the company's surface water tax has been applied in accordance with the current Tax Regulation, but the company is not yet fully in accordance with the applicable Regional Regulations because in the payment of surface water tax PT Air Manado still has arrears of surface water tax payments.